Asymptotic Rate of Convergence of a Two-Layer Iterative Method of the Variational Type - Zhuk, P. F.; Musina, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We present the definition and study the dependence on the initial approximation of the asymptotic rate of convergence of a two-layer symmetrizable iterative method of the variational type. The explicit expression is obtained for the substantial (with respect to the Lebesgue measure) range of its values. Its domain of continuity is described.